Los materiales didácticos en el proceso de enseñanza de las ciencias sociales - Chica Bravo, Adriana Melany (MACHALA, 2019)
Educational materials in the teaching process provide students with an amplified view of the society in which they live, their culture, location, origin and role in society. But there is a fear that there are still teachers who do not use teaching materials, continue to work with the traditional method making this education slow and uninnovative. There is a wide variety of teaching materials that a teacher can use freely and apply them in class, such as slides, blackboards and debates, etc. This type of material gives safety to the student, helps them to make decisions, to be creative and to solve doubts. As a resource that highlights among others this web, being an inexhaustible source of information and a resource of constant innovation for education. This can be applied for any of the subjects that the teacher sees necessary to better capture the attention of the students and thus to be able to develop their abilities and potentialities. That influence on the part of the teacher, the one who is always willing to help adjusting to the time and process of each of his students, causes that these achieve their objectives raised by achieving their own personal growth and for a Teacher there is nothing better than to see your students achieve success.
Los materiales didácticos en el proceso de enseñanza ofrecen a los estudiantes una visión amplificada de la sociedad en donde viven, su cultura, ubicación, origen y papel que toman en la sociedad. Pero existe un temor y es que aún existen docentes que no utilizan materiales didácticos, siguen trabajando con el método tradicional haciendo de esta educación lenta y poco innovadora. Existe gran variedad de materiales didácticos que un docente puede usar libremente y aplicarlos en clase, como las diapositivas, la pizarra y el debate, etc. Este tipo de materiales dan seguridad al alumno, los ayuda a tomar decisiones, a ser creativos y a resolver dudas. Como un recurso que resalta entre los demás esta la web, siendo una fuente inagotable de información y un recurso de innovación constante para la educación. Este puede ser aplicado para cualquiera de las asignaturas que el docente vea necesario para captar mejor la atención de los estudiantes y así poder desarrollar sus habilidades y potencialidades. Aquella influencia que se tiene por parte del docente, ese que está siempre dispuesto a ayudar ajustándose al tiempo y proceso de cada uno de sus estudiantes, provoca que estos logren alcanzar sus objetivos planteados consiguiendo su propio crecimiento personal y para un docente no hay nada mejor que ver a sus estudiantes alcanzar el éxito.
Keywords: ENSEÑANZA-APRENDIZAJE; RECURSO; ESTUDIO SOCIAL